Experimental and numerical study on square anchor plate groups in geogrid reinforced sand. Issue 6 (11th October 2019) - Choudhary, A. K.; Pandit, B.; Sivakumar Babu, G. L.
Abstract : The paper investigates the behaviour of groups of horizontal square anchor plates in geogrid-reinforced sand using laboratory model tests. The optimum spacing for two anchor plates in unreinforced sand is 3.4 times the anchor width. The unreinforced groups of anchor plates show a clear failure at a displacement of about 5% of the anchor width, whereas this value increases to more than 45% for reinforced groups along with a two-fold increase in uplift capacity. The optimum width and length of the geogrid reinforcement for groups of two anchors is found to be 5 and 9.4 times the width of the anchor plate, respectively. The performance improvement for isolated anchor plates is found to be maximum and gradually reduces with an increase in the number of plates; however, this reduction is much less in groups of two to four. Therefore, the results obtained from the model tests for reinforced groups of two to four anchor plates can be conveniently used to extrapolate the uplift capacity of multiple anchor plate systems in a reinforced soil mass. The model test results show a reasonably good agreement with the three-dimensional (3D) numerical analysis results.